Bước đầu nghiên cứu tổng hợp mafenit axetat qua trung gian phtalimit - Giang, Nguyễn Văn; Nghĩa, Hoàng Xuân; Hải, Nguyễn Văn; Luyện, Nguyễn Đình (Vietnam Journal of Chemistry, 2017)
Currently, topical antibacterial creams based on mafenide acetate are among the most common medicines used for the treatment of burns against approximately all pathogens colonized in burn wounds, including Pseudomonas aeruginosa and Clostridia. In this paper, mafenide acetate has been successfully synthesized through phthalimide intermediate. The structure of the intermediate derivatives and mafenide acetate were confirmed by IR, 1H-NMR, 13C-NMR spectroscopy and ESI-MS. Keywords. Mafenide acetate, burn, phthalimide, N-benzylphthalimide, chlorosulfonation.